Effects of increasing larval chironomid densities on the underwater feeding success of downy Tufted ducklings Aythya fuligula - Giles, N (Wildfowl, 1990)
This study relates the underwater feeding success of downy Tufted ducklings (aged 14-25 days) to differing levels of food (chironomid larvae) availability. Feeding success (chironomids caught per dive) increased from an average of about one at a prey density of 2000/m to six at 8000/m and around 12 at 16,000/m. Ducklings also increased their mean dive duration and total foraging effort with increasing prey density. Over the range of food densities used in the present experiments, ducklings showed no sign of becoming limited by time in their ability to catch more prey per dive at high prey densities. This study shows that despite dives only lasting around 3 seconds, ducklings still have time available to catch and handle up to 14 chironomid larvae per dive. At the highest food density tested ducklings could, by selecting the largest available larvae, fulfil their daily food requirement in 36 minutes of underwater foraging. This period is greatly affected by prey size and prey density. More experiments are needed to establish the food density at which feeding success reaches a plateau. These results are discussed in relation to the literature available for other wildfowl and wading bird species.